Partial reprogramming strategy for intervertebral disc rejuvenation by activating energy switch. Issue 4 (9th March 2022) - Cheng, Feng; Wang, Chenggui; Ji, Yufei; Yang, Biao; Shu, Jiawei; Shi, Kesi; Wang, Lulu; Wang, Shaoke; Zhang, Yuang; Huang, Xianpeng; Zhou, Xiaopeng; Xia, Kaishun; et al.
Abstract: Rejuvenation of nucleus pulposus cells (NPCs) in degenerative discs can reverse intervertebral disc degeneration (IDD). Partial reprogramming is used to rejuvenate aging cells and ameliorate progression of aging tissue to avoiding formation of tumors by classical reprogramming. Understanding the effects and potential mechanisms of partial reprogramming in degenerative discs provides insights for development of new therapies for IDD treatment. The findings of the present study show that partial reprogramming through short‐term cyclic expression of Oct‐3/4, Sox2, Klf4, and c‐Myc (OSKM) inhibits progression of IDD, and significantly reduces senescence related phenotypes in aging NPCs. Mechanistically, short‐term induction of OSKM in aging NPCs activates energy metabolism as a "energy switch" by upregulating expression of Hexokinase 2 (HK2) ultimately promoting redistribution of cytoskeleton and restoring the aging state in aging NPCs. These findings indicate that partial reprogramming through short‐term induction of OSKM has high therapeutic potential in the treatment of IDD. Abstract : Partial reprogramming through short‐term cyclic expression of Oct‐3/4, Sox2, Klf4, and c‐Myc (OSKM) inhibits the progression of intervertebral disc degeneration. Mechanistically, short‐term induction of OSKM in aging nucleus pulposus cells (NPCs) activates energy metabolism as a "energy switch" by upregulating expression of Hexokinase 2 (HK2) ultimately promoting redistribution of cytoskeleton and restoring the aging state in aging.